Affective design and sustainability: Social stimulation at the feet of humanity - Mourão, Nadia Maria; Mourão, Beatriz de Paula; Hoehne , Aline Mourão Lataro (Seven Editora, 2023)
A product can meet the fundamental and essential categories and requirements of the costumers without arousing or enjoying the relationship between product and consumer. This project searches for solutions of affective design and some impacts of projects that are related to footwear. UNICEF’s program "Guardians of Childhood" in Croatia raises awareness among consumers about the eradication of extreme poverty in Africa. Another example is the campaign called "Put yourself in her place" where a group of lawyers reported violations of the rights of domestic workers in Kuwait. The third example of a campaign is "Sustainable Footprint" of Adidas, which had great impacts in Sao Paulo and other cities where exists another store of the brand. It is important to highlight a sustainable contribution, in this case, an affective sustainability for the ethical concepts of consumption and creation of a pleasant bonding between the product and the user. DOI:https://doi.org/10.56238/interdiinovationscrese-042